On the mental representations of L2 English /z/ among L1 Chinese speakers - Yu-Leng Lin; Chin-Ting Liu (Acta Psychologica)
The study investigates how L1 Taiwan Mandarin speakers perceive the L2 English voiced /z/, whose counterpart is not directly available in Taiwan Mandarin. A transcription task was conducted to allow participants to freely choose Taiwan Mandarin segments they perceive as suitable substitutes for English /z/. Using a substitution pattern analysis, the study aims to understand the challenges faced by these speakers in acquiring English /z/. Three theoretical accounts—Feature Match Account, Auditory Salience Account, and Composite Phonetic Category Account—predicted differently regarding how L1 Taiwan Mandarin speakers might represent English /z/ in their mental grammar. The results indicate that /ts/ is frequently chosen as the optimal substitute for English /z/ in Taiwan Mandarin. An AXB discrimination task further revealed that the participants perceptually clustered English /z/ with the Mandarin segments /ts/, /ʐ/, and /s/, with /ts/ perceived as the closest match. The results suggest variability in category formation, with possible composite categories for English /z/ linked to Mandarin segments within a shared L1/L2 phonetic space. The perceptual boundaries between L1 and L2 categories appear fluid, reflecting ongoing interaction and competition in this shared phonetic space. This research contributes to our understanding of L2 speech perception strategies and the interplay between native and acquired language sounds.